Visualisation pattern guidelines for emotional engagement in e-learning website for higher education institutions - Alberto Aning (2023)
The research focuses on the scenario of e-learning websites, particularly within the context of Higher Education Institutions (HEIs). These websites face a significant challenge in engaging students, and there is a lack of user interface design guidelines that foster emotional engagement. As a result, student disengagement becomes a prevalent issue on these e-learning platforms. To address this problem, the research proposes the application of Kansei engineering (KE), a user-oriented technology that examines the emotional needs of consumers and establishes the relationship between emotions and product design elements. By utilizing KE principles in the design process of e-learning websites, the goal is to create a positive emotional impact on users, eliciting feelings of delight, engagement, trust, and contentment. The objective of the research is to develop a guideline specifically for the user interface design (UID) of e-learning websites in HEIs. This guideline aims to assist website developers and designers in creating e-learning platforms that sustain students' interest and engagement over time. To evaluate the effectiveness of the proposed UID guideline, the research conducted an evaluation using an electroencephalogram (EEG) device. The results showed that 65% of the participants fell into the "Most Effective" category, with the highest average effectiveness rating reaching 32.6%. These findings demonstrate that the developed guideline significantly increased student engagement with the UID of the e-learning website prototype. Overall, the research emphasizes the importance of considering emotional engagement in the design of e-learning websites. By incorporating Kansei engineering principles, HEIs and website developers can create e-learning platforms that effectively capture and sustain students' interest, thereby enhancing the overall effectiveness of e-learning experiences.